2014
DOI: 10.3389/fnhum.2014.00611
|View full text |Cite
|
Sign up to set email alerts
|

EEG spectral analysis of attention in ADHD: implications for neurofeedback training?

Abstract: Objective: In children with attention-deficit/hyperactivity disorder (ADHD), an increased theta/beta ratio in the resting EEG typically serves as a rationale to conduct theta/beta neurofeedback (NF) training. However, this finding is increasingly challenged. As NF may rather target an active than a passive state, we studied the EEG in a condition that requires attention.Methods: In children with ADHD of the DSM-IV combined type (ADHD-C; N = 15) and of the predominantly inattentive type (ADHD-I; N = 9) and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
2
42
0
1
Order By: Relevance
“…By contrast, combined EEG-fMRI studies in healthy subjects have found positive correlations between the functional activity of the DMN and the amplitude of EEG theta-alpha rhythms (4-12 Hz) [131][132][133] . Hence, an excess of task-related theta-alpha rhythms 115,134 , which may be reflective of an abnormally upregulated DMN, might be one candidate mechanism responsible for attentional deficits in ADHD. Interestingly, a recent EEG-fMRI study showed that suppressed alpha-rhythm amplitudes after neurofeedback training predicted reduced mind-wandering and were associated with upregulation of task-positive networks and downregulation of the DMN 18 .…”
Section: Fugl-meyer Scoresmentioning
confidence: 99%
“…By contrast, combined EEG-fMRI studies in healthy subjects have found positive correlations between the functional activity of the DMN and the amplitude of EEG theta-alpha rhythms (4-12 Hz) [131][132][133] . Hence, an excess of task-related theta-alpha rhythms 115,134 , which may be reflective of an abnormally upregulated DMN, might be one candidate mechanism responsible for attentional deficits in ADHD. Interestingly, a recent EEG-fMRI study showed that suppressed alpha-rhythm amplitudes after neurofeedback training predicted reduced mind-wandering and were associated with upregulation of task-positive networks and downregulation of the DMN 18 .…”
Section: Fugl-meyer Scoresmentioning
confidence: 99%
“…This hypothesis is gaining momentum. A recent review (Lenartowicz et al., ) identified 12 published studies since 2009, spanning adult and child samples, to document weakened alpha power modulation during encoding in tasks of cued selective attention (Mazaheri et al., ; Yordanova, Kolev, & Rothenberger, ), visual interference (i.e., flanker)(Hasler et al., ; Heinrich et al., ; Mazaheri et al., ), spatial working memory (Gomarus, Wijers, Minderaa, & Althaus, ; Lenartowicz et al., , ; Missonnier et al., ), as well as spatial visual attention (ter Huurne et al., ; Ter Huurne et al., ; Vollebregt et al., ). Consistent with our results, alpha power deficits have been associated with inattentive symptoms, suggesting that this metric is sensitive to typical behavioral dysfunction in ADHD (Gomarus et al., ; Lenartowicz et al., ; Mazaheri et al., ; Ter Huurne et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is gaining momentum. A recent review (Lenartowicz et al, 2018) identified 12 published studies since 2009, spanning adult and child samples, to document weakened alpha power modulation during encoding in tasks of cued selective attention Yordanova, Kolev, & Rothenberger, 2013), visual interference (i.e., flanker) (Hasler et al, 2016;Heinrich et al, 2014; Higher score indicates fewer attention problems, thus greater alpha decrease during encoding, is associated with fewer ADHD symptoms). b Cronbach's alpha for each measure calculated on comparison of odd-numbered trials with even-numbered trials within each participant and is reported for low-load/high-load conditions.…”
Section: Alpha Power and Attentional Healthmentioning
confidence: 99%
“…The aim of the theta/beta training is to decrease the strength of central theta band power and to increase beta oscillations. The rationale for this is that children with ADHD have been observed to have increased theta power accompanied by reduced beta power, which has been interpreted as a sign of cortical hypoarousal (Hammond, ; Heinrich et al., ).…”
mentioning
confidence: 99%